PRAKTIK PROFESI ASUHAN KEPERAWATAN KOMUNITAS DI RW 003 KELURAHAN SANGIANG JAYA KECAMATAN PERIUK KOTA TANGERANG 20 NOVEMBER – 22 DESEMBER 2023 - Janiah; Ubaydilah; Fachrul Aulia; Ibnu Rizal Syarifudin; Sopian Sauri; Dwi Sagita Apriyani; Tsani Dermawan; Imas Permasi; Dwi Setyawati; Anik Widiastuti; Nur Hafidiani; Chaerunnisa Eka Sania; Ati Setiawati; Yeni Gumiati; Afrina Kusuma Dewi; Rina Puspita Sari (Yayasan Nusantara Hasana Berdikari, 2024)
Background: Community health nursing is a professional nursing service provided holistically (bio, psycho, social and spiritual) and focused on high risk groups which aims to improve health status through promotive and preventive efforts without neglecting curative and rehabilitative by involving the community as partners in solve health problems that occur in society. Research Objective: To provide an overview of community nursing care in increasing the level of optimal healthy living in the community of RW 003, Sangiang Jaya Village, Periuk District, Tangerang City. Research Results: After carrying out hypertension exercises for three days, the results were obtained before carrying out physical activity in the form of hypertension exercises, the blood pressure of the residents of RW 03 Sangiang Jaya, Periuk, Tangerang was 6 people BP 100-120, 8 people BP >120-140 and 9 people BP >150 mmHg, but after doing hypertension exercises for 3 days it showed that 9 people had BP 100-120, 12 people had BP >120-140, and 2 people had BP >150 mmHg. It can be concluded that there was a decrease in BP after doing hypertension exercises for 3 days.